2019
DOI: 10.14502/tekstilec2019.62.12-22
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional Hydrophobic, Oleophobic and Flame-retardant Polyester Fabric

Abstract: Technical textile materials with multifunctional protective properties represent one of the largest and fast growing segments of the textile industry. Multifunctional water-and oil-repellent and fl ame-retardant coating on polyester (PES) fabric was prepared in this research using fl uoroalkyl-functional siloxane (FAS) as the water-and oil-repellent fi nishing agent and organophosphonate (OP) as the fl ame-retardant agent. A fi nishing solution containing FAS and OP of appropriate concentrations was applied to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Moreover, the consumed chemical amount was half of the maximum concentration without the LOI changing significantly. In work [ 21 ], an organophosphonate (OP), as the FR agent, was applied to the untreated and oxygen plasma-treated polyester fabric samples using the pad-dry-cure method. The results reveal that oxygen plasma treatment prior to finishing significantly increased the wettability of the polyester fibers, which directly resulted in increased concentration of the absorbed finishing agents.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the consumed chemical amount was half of the maximum concentration without the LOI changing significantly. In work [ 21 ], an organophosphonate (OP), as the FR agent, was applied to the untreated and oxygen plasma-treated polyester fabric samples using the pad-dry-cure method. The results reveal that oxygen plasma treatment prior to finishing significantly increased the wettability of the polyester fibers, which directly resulted in increased concentration of the absorbed finishing agents.…”
Section: Introductionmentioning
confidence: 99%
“…This allows the plasma pretreated sample to have better FR properties than those of the control sample. Thus, works [ 4 , 19 , 20 , 21 ] have shown that the plasma pretreatment for polyester fabric improves the efficiency of the subsequent flame retardant treatment despite using different types of plasma and flame retardants. However, plasma pretreatment for PET fabric can also have undesirable effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation